DIGITAL EVIDENCE - Lukić, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Computers make human activity faster, easier and more interesting and with their help to create new models of work and other kinds of human activity,and therefore criminal activity. All those technologies which carry information and the information revolution are both carriers of the evolution of computer forensics, which allows us to detect and prove the crimes committed by computer and capture the perpetrators. Combat against nowadays forms of crime in which computers are not necessarily appear as an asset or objective of the offense, necessarily requires knowledge of digital evidence as well as specific rules and procedures for detecting, fixing andcollecting of the information technologyprofessionals. Bearing this in mind, the author of this article specifically addresses the issues of digital evidence, forensic (computer) investigation and use of this type of evidence in criminal proceedings. Computer forensics is a type of forensics is the application of computer investigation and analysis techniques to identify potential evidence. It can be defined as a process of collecting, preserving, analyzing and presenting digital evidence in court proceedings. Computer forensics involves the investigation of a misuse of information technologies based on digital evidence. It is the application of computer investigation and analysis techniques to identify potential evidence. Digital evidence is material evidence of electronic or electromagnetic type and for their pripkupljanje need special equipment. Digital evidence is information relevant to the investigation, which is stored in digital form. Such evidence undoubtedly consist of high-tech gadgets that require a different type of investigation and faces a special expertise. When forensic experts take all necessary measures to ensure the integrity of the evidence, even beyond those measures required by the court as a threshold of acceptability, such evidence is provided eligibility. Evidence gathered at the scene, as well as operational knowledge determines the direction of further investigation.